If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -6)(2x + 9) = 0 Reorder the terms: (-6 + 5x)(2x + 9) = 0 Reorder the terms: (-6 + 5x)(9 + 2x) = 0 Multiply (-6 + 5x) * (9 + 2x) (-6(9 + 2x) + 5x * (9 + 2x)) = 0 ((9 * -6 + 2x * -6) + 5x * (9 + 2x)) = 0 ((-54 + -12x) + 5x * (9 + 2x)) = 0 (-54 + -12x + (9 * 5x + 2x * 5x)) = 0 (-54 + -12x + (45x + 10x2)) = 0 Combine like terms: -12x + 45x = 33x (-54 + 33x + 10x2) = 0 Solving -54 + 33x + 10x2 = 0 Solving for variable 'x'. Factor a trinomial. (-9 + -2x)(6 + -5x) = 0Subproblem 1
Set the factor '(-9 + -2x)' equal to zero and attempt to solve: Simplifying -9 + -2x = 0 Solving -9 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = 0 + 9 -2x = 0 + 9 Combine like terms: 0 + 9 = 9 -2x = 9 Divide each side by '-2'. x = -4.5 Simplifying x = -4.5Subproblem 2
Set the factor '(6 + -5x)' equal to zero and attempt to solve: Simplifying 6 + -5x = 0 Solving 6 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 0 + -6 -5x = 0 + -6 Combine like terms: 0 + -6 = -6 -5x = -6 Divide each side by '-5'. x = 1.2 Simplifying x = 1.2Solution
x = {-4.5, 1.2}
| 0=-0.125x^2+0.35x+0.75 | | 4(x-2)4x+10= | | Log(x^2-9)-log(x+3)=3 | | y=-0.125x^2+0.35x+0.75 | | -2v+34=8(v+3) | | (4x^2-3x^3)-(8x^2-5x^3)= | | 17z-6z+3= | | 5w^2-3w=17 | | 9x^2/lnx | | 8(u+4)=-2u+12 | | 100=-0.1x+1 | | x^2-12x+36=352 | | -3x=12x+-8+1 | | 3=-0.1x+1 | | 45=-0.1x+1 | | 300x-0.04=500x+0.18 | | -3x=x+-8+1 | | 35=w^2+3w | | (z^2/3)(z^1/4) | | 5wsquared=17 | | 2(x-3)+8x=-36 | | x^2+7x+3=-7 | | X+4=5(4x-2) | | Y=-0.1(420)+1 | | 8(u+2)-4u=-24 | | X-9=-6+-5 | | -25=4(w-8)+3w | | Y=-0.1(600)+1 | | 9/2x=60 | | 34=8(y+5)-6y | | 0.2x+25=9 | | m^2-10m+10=14 |